Angiotensin-converting enzyme and human physical performance - Payne, J.; Montgomery, H. (Equine and Comparative Exercise Physiology, 2004)
Genes undoubtedly play a role in the development of a successful athlete. This view has flourished on anecdotes such as the observation of a child who displays the same aptitude for a particular sport as one of their parents, or a pair of sisters who both excel in the same discipline. However, the conclusions made from this type of observation have an obvious limitation: that similar environmental factors may be just as responsible as genetic inheritance in explaining the passage and sharing of talent between family members. Here, we review briefly the salient data showing that genes do play a role in athletic performance, and although the data examining the effect of specific genes are limited, we present data examining the role of the angiotensin-converting enzyme gene in human physical performance.